Artificial sweeteners affect the glucose transport rate in the Caco‐2/NCI‐H716 co‐culture model. (13th July 2020) - Xie, Ningning; Huang, Xi; Yang, Chuyi; Dai, Minchen; Cai, Lei; Deng, Shaoping; Hardiman, Paul J; Zhou, Jue
Abstract: BACKGROUND: Artificial sweeteners have been used widely as substitutes for sugar for several decades. In recent years they have been reported to be harmful to human health – especially to glucose absorption. However, as conclusions from previous studies using a single Caco‐2 cell model were not consistent, further studies with a more suitable cell model are needed. RESULTS: We established a co‐culture model with enterocyte Caco‐2 and enteroendocrine NCI‐H716 cell lines cultured in transwell inserts. The effects of artificial sweeteners, enhancing the glucose transport rate, lasted for 60 min and then began to diminish. Most importantly, different artificial sweeteners with the same sweetness intensity had similar effects on glucose transport. The sodium / glucose co‐transporter member 1 (SGLT1) mRNA expression levels increased significantly with an initial glucose concentration of 20 mM, while glucose transporter 2 (GLUT2) mRNA expression significantly increased with initial glucose concentrations of 20 mM and 60 mM. CONCLUSION: Based on the Caco‐2/NCI‐H716 co‐culture model, SGLT1 and GLUT2 mediated the enhancing effects of artificial sweeteners on glucose transport, depending on the sweetness intensity and initial glucose concentration.